2018
DOI: 10.1186/s13287-018-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

Linking cell function with perfusion: insights from the transcatheter delivery of bone marrow-derived CD133+ cells in ischemic refractory cardiomyopathy trial (RECARDIO)

Abstract: BackgroundCell therapy with bone marrow (BM)-derived progenitors has emerged as a promising therapeutic for refractory angina (RA) patients. In the present study, we evaluated the safety and preliminary efficacy of transcatheter delivery of autologous BM-derived advanced therapy medicinal product CD133+ cells (ATMP-CD133) in RA patients, correlating perfusion outcome with cell function.MethodsIn the phase I “Endocavitary Injection of Bone Marrow Derived CD133+ Cells in Ischemic Refractory Cardiomyopathy” (RECA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Indeed, a consistent body of evidence (RCT and MTA) cumulatively indicated that CT is safe and can effectively increase physical function and well-being by reducing angina symptoms and drug assumption in the absence of relevant side effects ( 18 ). Different pro-angiogenic cells were administered in an autologous setting, including unfractioned bone marrow (BM)-derived mononuclear cells (MNC) ( 99 , 100 ), selected endothelial progenitors (i.e., CD34 + and CD133 + cells) derived from BM or peripheral blood ( 101 104 ) or mesenchymal stem cells derived from BM ( 105 ) or adipose tissue ( 106 108 ) ( Figure 1 ). In addition to pilot and proof-of-concept clinical studies, a significant proportion of published trials may be categorized as phase II RCT ( 100 , 101 , 109 111 ).…”
Section: The Case Of Cell Therapymentioning
confidence: 99%
“…Indeed, a consistent body of evidence (RCT and MTA) cumulatively indicated that CT is safe and can effectively increase physical function and well-being by reducing angina symptoms and drug assumption in the absence of relevant side effects ( 18 ). Different pro-angiogenic cells were administered in an autologous setting, including unfractioned bone marrow (BM)-derived mononuclear cells (MNC) ( 99 , 100 ), selected endothelial progenitors (i.e., CD34 + and CD133 + cells) derived from BM or peripheral blood ( 101 104 ) or mesenchymal stem cells derived from BM ( 105 ) or adipose tissue ( 106 108 ) ( Figure 1 ). In addition to pilot and proof-of-concept clinical studies, a significant proportion of published trials may be categorized as phase II RCT ( 100 , 101 , 109 111 ).…”
Section: The Case Of Cell Therapymentioning
confidence: 99%
“…Trans-endocardial delivery of another autologous bone marrow-derived cells, CD133+ cells, were proved to be safe and feasible in two small phase I randomized trials not powered for efficacy end-points [82,83]. Another recent phase I randomized trial of intramyocardial injection of CD133+ cells in RA patient subset with LV dysfunction (LV < 45%) confirmed the safety profile of the previous two trials and showed significant improvements in CCS angina class, myocardial perfusion and function assessed by single-photon emission computer tomography at 12 months [84]. Moreover, improvements in myocardial perfusion were positively correlated with the proangiogenic growth factors, hepatocyte growth factor and platelet-derived growth factor type bb, substances involved in neovascularization, endothelial and muscle cell growth [85,86].…”
Section: Stem Cell Therapymentioning
confidence: 84%
“…A considerable number of recent clinical trials in stem cell therapy for HF have demonstrated its promise and substantially increased our understanding of the behaviors and working mechanisms of stem/progenitor cells in patients ( Table 1 ). ( Hamshere et al, 2015 ; Martino et al, 2015 ; Perin et al, 2015 ; Choudry et al, 2016 ; Noiseux et al, 2016 ; Patel et al, 2016 ; Bartolucci et al, 2017 ; Butler et al, 2017 ; Choudhury et al, 2017 ; Florea et al, 2017 ; Gwizdala et al, 2017 ; Hare et al, 2017 ; Steinhoff et al, 2017 ; Teerlink et al, 2017 ; Xiao et al, 2017 ; Bassetti et al, 2018 ; Vrtovec et al, 2018 ; Yau et al, 2019 ; Bolli et al, 2020 ; He et al, 2020 ; Makkar et al, 2020 ; Mathiasen et al, 2020 ; Ulus et al, 2020 ; Bolli et al, 2021 ; Qayyum et al, 2023a ; Qayyum et al, 2023b ; Perin et al, 2023 ) In the next phase of clinical stem cell research, it is critical to address the outcome discrepancy between preclinical and clinical studies and expand the scope of stem cell-based therapy to other forms of cardiomyopathy, such as chemotherapy- or arrhythmia-induced cardiomyopathy. Exploiting the power of AI/ML and computational tools will facilitate our understanding of the benefits and limitations of stem cell therapy and provide a systems perspective for properly applying stem cell therapeutics in the context of precision and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%